1982
DOI: 10.1007/bf02535357
|View full text |Cite
|
Sign up to set email alerts
|

Sphingolipids in immature and mature soybeans

Abstract: Ceramides and cerebrosides were isolated from immature and mature soybeans, and structures of the constituents were investigated. As component fatty acids, normal, 2‐hydroxy and 2,3‐dihydroxy acids were found in ceramides, whereas only normal and 2‐hydroxy acids were identified in cerebrosides. The principal fatty acid component was 2‐hydroxylignoceric acid in ceramides, and 2‐hydroxypalmitic acid in cerebrosides. Sphingoids in ceramides consisted mainly of trihydroxy bases, with 4‐hydroxy‐trans‐8‐sphingenine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
3

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(56 citation statements)
references
References 21 publications
2
51
3
Order By: Relevance
“…TLC on silica gel G with chloroformmethanol (95: 12, v/v) of CM and G1CM isolated from rice grains gave at least three spots,6) Rfvalues of which were identical with the authentic ones prepared from soybean seeds 9 ) and Aspergillus oryzae. 18 ) When oligoglycosylceramides from rice grains were used for TLC (Fig.…”
Section: Confirmation Of Sph Ingo Lip Idsmentioning
confidence: 73%
See 1 more Smart Citation
“…TLC on silica gel G with chloroformmethanol (95: 12, v/v) of CM and G1CM isolated from rice grains gave at least three spots,6) Rfvalues of which were identical with the authentic ones prepared from soybean seeds 9 ) and Aspergillus oryzae. 18 ) When oligoglycosylceramides from rice grains were used for TLC (Fig.…”
Section: Confirmation Of Sph Ingo Lip Idsmentioning
confidence: 73%
“…The mass spectra of the second major peak (22%) gave the base peak at mjz 204 and notable ions at mj z 1332 (M -15) indicating the molecular weight, at mjz 1050 and 297 due to the sphingoid moiety, and at mjz 528 and 570 derived from the component fatty acid. 9 ,zO,Zl) From these ions the peak species was identified as 1-0-glucosyl-N"2' -hydroxylignoceroyl-4-hydroxysphingenine. Likewise, mass spectrometric data of the other peak lipids were assayed and are summarized in Table V.…”
Section: Principal Molecular Species Of CM and G 1 Cmmentioning
confidence: 99%
“…Similarly, in the few cases where cis-trans isomerization of long-chain bases has been reported, the trans isomer oft 18:1 is typically more abundant than the cis isomer (e.g. 8,[23][24][25]. In addition, the composition of intact glucocerebroside molecular species detected in the leaf and plasma membrane of rye were similar.…”
Section: Gc/ms Identification Of Glucocerebroside Molecular Speciesmentioning
confidence: 89%
“…In a previous study (18), glucocerebrosides were reported to constitute 16 mol% of the plasma membrane lipid of cells of noncold-acclimated rye leaves. It was also suggested that this lipid may be of importance in altering cryostability of rye plasma membrane (18,30 (29), Phaseolus vulgaris (5), and spinach (25) as well as seeds of Azuki bean (23), pea (1 1), and soybean (24) consist almost entirely of saturated 2-hydroxy fatty acids. Similarly, in the few cases where cis-trans isomerization of long-chain bases has been reported, the trans isomer oft 18:1 is typically more abundant than the cis isomer (e.g.…”
Section: Gc/ms Identification Of Glucocerebroside Molecular Speciesmentioning
confidence: 99%
“…CMH is known to be widespread in plants, although the content is usually low (4)(5)(6)17). It has been reported that plasma membrane and tonoplast contain CMH (8,12,15,30).…”
Section: Discussionmentioning
confidence: 99%